Od feudalizmu do afrykańskiego sposobu produkcji. Problem typologii przednowoczesnych peryferyjnych społeczeństw europejskich - Babinskas, Nerijus (Człowiek i Społeczeństwo, 2016)
I assert that methodological nationalism (national paradigm) is one of the main reasons of methodological inertia of the current historiography especially in the area of the post-communist European countries. In the current article I argue that comparative history could be a bridge between conventional (mainstream) historiography and approaches of so-called macrohistory. In this context typology should be treated as one of possible methods of comparative history. The most traditional approach of medievalists to articulate classification of pre-modern European societies is consider whether particular pre-modern society is feudal or not. However I argue that this approach is quite complicated because of ambiguity and polysemy of the term. There are at least several Marxist and non-Marxist alternatives like the tributary mode of production, patrimonialism versus feudalism dichotomy or the so-called type/model of early Central European state. The application of the concept of the African mode of production in the case of typology of some European pre-modern peripheral societies despite of its paradoxically looking etimology also is plausible.